Efektivitas Comic Book: BW (Brisk Walking) Terhadap Social Support dan Perubahan Kontrol Gula Darah (Gula Darah Puasa) Pada Pasien Diabetes Melitus Tipe 2 - Zainuddin; Ernawati; Meylandri Arsad, Sitti Fatimah; Suardi; Aswadi; Syahrir, Sukfitrianty (Al GIZZAI: PUBLIC HEALTH NUTRITION JOURNAL, 2024)
Type 2 Diabetes Mellitus (T2DM) is a group of metabolic diseases characterized by hyperglycemia due to impaired insulin secretion, or both, so it requires direct intervention with educational media. The effectiveness of Comic Books in encouraging T2DM patients to (Brisk walking) has a positive impact on blood sugar control. This research aims to determine the effectiveness of Comic Book: BW (Brisk Walking) and Social Support on Changes in GDP Control (Fasting Blood Sugar) in Type 2 Diabetes Mellitus Patients in Takalar Regency. This research method is quasi-experimental using a two group pre-test and post-test design approach with a purposive sampling method of 30 respondents in the intervention group and 30 respondents in the control group. Data collection in this study used a questionnaire, and data analysis used the T-Test. The results of this research show that there is significant effectiveness between Social Support and GDP in giving Comic Books: (Brisk Walking). The conclusion of this research results is a reference and evidence-based practice for health services to increase insight in improving care for T2DM patients through comic book media.